Occurrences of Sea turtles in Azores Archipelago - Barcelos, Luis M. D. (2022)
Sea turtles are the best-known and more widespread marine reptiles. However, information on their distribution and the occurrence of most species, except for nesting beaches, remains scarce and sporadic, depending on sightings from fishing vessels, tourist activities and occurrences in coastal areas as well as fishing bycatch. Since the last updated species’ list for the Azores (Santos et al, 2010), no new species’ record was known for Azorean waters, until October 2020, with the confirmed sighting of an Olive Ridley, Lepidochelys olivacea (Eschscholtz, 1829) (Barcelos et al. 2021). After that, in February 2021, a second individual was found stranded on Pico Island, already in an advanced state of decomposition. This increased the number of species present in Azores EEZ (Exclusive Economic Zone) to six out of the seven extant worldwide. The remaining one, Natator depressus (Garman, 1880), is native to the Indo-pacific (see Red List Standards & Petitions Subcommittee, 1996).